New Achievements in Continuum Mechanics and Thermodynamics A Tribute to Wolfgang H. Müller - Abali, Bilen Emek.; Altenbach, Holm.; dell'Isola, Francesco; Eremeyev, Victor A.; Öchsner, Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a liber amicorum dedicated to Wolfgang H. Müller, and highlights recent advances in Prof. Müller's major fields of research: continuum mechanics, generalized mechanics, thermodynamics, mechanochemistry, and geomechanics. Over 50 of Prof. Müller's friends and colleagues contributed to this book, which commemorates his 60th birthday and was published in recognition of his outstanding contributions.
1 Introduction -- 2 The continuum mechanics, and generalized mechanics -- 3 The mechano chemistry, and geomechanics.
Keywords: Mechanics, Applied; Solids; Materials -- Analysis; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Solid Mechanics; Characterization and Analytical Technique; Engineering Thermodynamics, Heat and Mass Transfer